2020
DOI: 10.1515/med-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lncRNA HOTAIR in colorectal cancer : a meta-analysis

Abstract: AbstractAbstract: HOX transcript antisense intergenic RNA (HOTAIR) is one of the most studied long noncoding RNAs (lncRNAs) and is aberrantly expressed in colorectal cancer (CRC). We thus performed a comprehensive study based on meta-analysis and validation of the TCGA database to investigate clinicopathological and prognostic value of HOTAIR in CRC. Six studies enrolling 629 CRC patients were included in the analysis. The results indicated that high HOTAIR expression predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…36 Some lncRNAs, such as lncRNA HOTAIR, lncRNA PVT1, circulating lncRNA DANCER, and others, can act as prognostic factors in CRC. 25,37,38 Although there have been many studies on the associations between lncRNAs and CRC, the roles and mechanisms of lncRNAs in CRC and their clinical applications still need extensive exploration. Recently, studies have reported different genetic models for predicting human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…36 Some lncRNAs, such as lncRNA HOTAIR, lncRNA PVT1, circulating lncRNA DANCER, and others, can act as prognostic factors in CRC. 25,37,38 Although there have been many studies on the associations between lncRNAs and CRC, the roles and mechanisms of lncRNAs in CRC and their clinical applications still need extensive exploration. Recently, studies have reported different genetic models for predicting human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Through further processing of deleting missing items in the clinicopathological data, a total of 392 cases of TCGA-CRC and 550 cases of GSE39582 were obtained ( Table 1 ). The metabolism-related genes are obtained from the GSEA website: First, download all KEGG pathway related genes (KEGG gene sets, gene symbols option) from the GSEA website ( https://www.gsea-msigdb.org/gsea/downloads.jsp ), which contains a total of 186 KEGG pathways (41 pathways are metabolically related, and 145 pathways are non-metabolically related); then extract the metabolic pathways All genes in are metabolic-related genes ( S1 Table ), which are used as metabolic gene expression data sets for subsequent analysis [ 16 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Overall, compelling evidence points to a potential role of HOTAIR as a biomarker for CRC prediction and diagnosis, due to its detection in bodily fluids [ 99 , 100 ], prognosis [ 101 ], and as a potential therapeutic target for the development of novel strategies to target its overexpression [ 94 , 98 ]. So far, a patent has been filed for HOTAIR in gastric cancer diagnosis [ 12 ], encouraging the development of novel applications.…”
Section: Validated Lncrna Candidates In Crcmentioning
confidence: 99%